TASK-BASED LANGUAGE TEACHING (TBLT) TO INCREASE ENGLISH SPEAKING SKILL OF INDONESIAN SECONDARY HIGH SCHOOL STUDENTS - Sabaruddin; Rahma Melati (LP2M Institut Agama Islam Muhammadiyah Sinjai, 2022)
The aim of this study is to investigate the benefits and challenges of Task-Based Language Teaching (TBLT) in the development of students’ speaking ability in Indonesian Secondary School Context. This study used comprehensive literature review from various sources. From the discussion, it is informed that TBLT is useful to increase English speaking competence of students. Firstly, TBLT is applicable to fosters students’ oral fluency. Secondly, TBLT can improves the speaking accuracy of students. Thirdly, TBLT helps students to enhance their speaking confidence. However, several challenges need to be addressed by the English teachers in order to use TBLT effectively. The finding of this study provides valuable literature for English teachers in Indonesia regarding the use (benefits and challenges) of TBLT to teach speaking skill.